Railway ballast anisotropy testing via true triaxial apparatus. (June 2020) - Yu, Zelong; Connolly, D.P.; Woodward, P.K.; Laghrouche, O.; Tutumluer, E.
Abstract: This paper aims to demonstrate the anisotropic behaviour of railway ballast via true-triaxial tests. To do so, a novel, large-scale, true-triaxial testing apparatus (GeoTT) is designed and constructed. It consists of six hydraulic actuators, designed to apply a distributed stress to large granular cubic test specimens with dimensions: 500 mm × 500 m × 500 mm. To show the capability of the new facility, crushed granite railway ballast with d50  = 43 mm is tested. Three different confining stresses are applied to determine the Poisson's ratio and modulus in three dimensions. Anisotropic behaviour is clearly evident, with horizontal directions showing a lower modulus compared to the vertical direction. It is also found that confining stress has an important effect on both Poisson's ratio and modulus when the primary loading is applied in three orthogonal directions. These results are useful for understanding the behaviour of railway ballast and for the calibration of railroad numerical models.